ANALYSIS OF EFFECTIVENESS, REGIONAL RETRIBUTIONS ON PAD AND REGIONAL SELF-RELIANCE IN LOMBOK UTARA DISTRICT 2017-2019 - Sari, Sejati Ratna; Sarah NH, Siti; Andini, Yudita Septia; Rizky, Try Rakhma; Alfan, Muhammad (Journal of Finance, Economics and Business, 2022)
The purpose of this study is to examine how effective local taxes and local fees are for PAD in the North Lombok district from 2017 to 2019, and the degree of local independence. This type of study uses quantitative statements that are analyzed using local financial independence rates, local independent income efficiency rates, and activity rates. According to the survey results, Lombok's Utara district still has not achieved independence, and the implementation of local autonomy relies heavily on the support of the central government through compensation funds. The effective rate still tends to be less effective and the activity rate is higher than the cost of capital rate. It is hoped that the North Lombok county government will be able to continue to increase his PAD yield and prioritize the allocation of regional spending.